Teaching English in Kindergarten by Using Games at PAUD TAQIFA Bangkinang Kota - Marleni, Lusi; Hardi, Vitri Angraini; Sari, Nurhidayah (Universitas Pahlawan Tuanku Tambusai, 2020)
The objective of this research was to know the effect of using Project-based Learning (PjBL) method on students’ writing skill of second year students at SMAN 2 Tapung Hilir. The design of this research was experimental research which was deal with two variables. The first variable was project based learning method as independent variable and the second variable was students’ writing skill as dependent variable. The sample of this research was 61 students of second year students at SMAN 2 Tapung Hilir. Further, there were two classes of this research. There were experimental class and control class. To obtain the data, the researcher gave the students explanation text as writing test. The data was analyzed by using paired sample T-test through SPSS 22 version program. Based on result shown that towas8.682 and df was 29. It could be analyzed that to is higher than ttable, of 0,05 on the significance rtable(8.682>0.367), that null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. It can be concluded that there is significant effect of using PjBL method on students’ writing skill of second year students at SMAN 2 Tapung Hilir.